Energy expenditure during virtual reality exergaming in adolescents with Autism Spectrum Disorder - Chernik, N. D.; Gonzalez, S.; Stout, R.; Lopez, A. (Frontiers in Virtual Reality, 2025)
IntroductionChildren and adolescents with Autism Spectrum Disorder face challenges throughout their development. Autism Spectrum Disorder can affect a multitude of areas, including social, cognitive, and physical. Due to delays in development, poor motor coordination, hypersensitivities, and difficulties with motivation and focus, these individuals are uninspired and discouraged to partake in physical activity. This lack of interest can lead to further impairments in health and developing social skills. This study evaluated the effect of virtual reality on exercise, specifically the effects on actual energetic output and perceived energetic output.MethodsEleven participants aged 8–19 with Level 1 Autism Spectrum Disorder completed two walking trials on a treadmill. The control trial did not have participants wear a virtual reality headset or interact with any games. The virtual reality trial allowed participants to play an interactive virtual reality game while walking on the treadmill. To measure actual metabolic output, energetic costs were measured by calculating cost of locomotion, cost of transport, and youth metabolic equivalents via open flow respirometry. To measure perceived levels of exertion, participants were asked to rate their exertion level using the Borg Rating of Perceived Exertion scale throughout the duration of the trials.ResultsA statistically significant increase was observed in all energetic measures during the virtual reality walking trials compared to the control trials (all p-values <0.020). Differences in perceived exertion were not statistically significant between the two experimental conditions.DiscussionThese findings suggest that in this patient population, virtual reality can help promote more intense and energetically costly physical activity, while having no effect on perceived exertion levels. These findings may be explained by multiple factors, including virtual reality acting as a distractor, the novelty aspect, or the effects of dual-task cognitive and motor activity.